Phase Engineering from 2H to 1T-MoS2 for Efficient Ammonia PL Sensor and Electrocatalyst for Hydrogen Evolution Reaction. Issue 8 (1st January 2019) - Chacko, Levna; Rastogi, Pankaj Kumar; Aneesh, P. M.
Abstract : In the recent years, phase transitions in MoS2 from 2H to 1T has gained considerable research interest that finds significant technological applications. This paper describes the development of active 1T MoS2 exhibiting metallic behavior from the semiconducting 2H MoS2 by simple two-step hydrothermal method without adding any additional atoms. This strain induced synthesis method allows the modification of the crystal phase and facilitate the electron transfer with reduced resistance of 89 Ω. We studied the formation of 1T MoS2 nanostructures using X-ray diffraction, spectroscopic and microscopic scientific tools. The metallic 1T phase is found to exhibit markedly high optoelectronic properties demonstrating an excitation wavelength dependent down-conversion and up-conversion photoluminescence. The large surface area, tunable bandgap, high electron mobility and increased active sites of 1T MoS2 elucidates a viable designing of optical photoluminescence ammonia sensing. Finally, we investigated the integration of 1T polymorph into an efficient electrocatalytic hydrogen evolution system to compare their catalytic activity with that of 2H MoS2 . 1T MoS2 is found to exhibit a low onset potential of 240 mV vs RHE than the 2H phase with a comparatively high onset potential of 550 mV vs RHE. The superior activity of 1T MoS2 owing to the abundant catalytic edge sites are critical for global production of clean and renewable energy sources.